Implementation of the Jigsaw Type Cooperative Learning Model to Improve Student Learning Outcomes at SD Negeri 101237 Rambasihasur - Hasibuan , Anita Tohiroh; Jelita, Rohana; Pane, Ramayu Dumilah (MADINA : Journal of Islamic Studies, 2024)
This research aims to improve student learning outcomes in Islamic religious education learning by using jigsaw type cooperative learning. This research is classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this research were elementary school students. This research data was obtained using test and observation techniques. Tests are used to measure learning outcomes and observations are used to analyze teacher and student learning activities. The data analysis technique used in this research is descriptive statistics by comparing the results obtained with indicators of research success. The results of the research show that jigsaw type cooperative learning can improve student learning outcomes in Islamic religious education learning. This can be seen from the increase in the percentage of student learning completeness in each cycle with details of pre-cycle 41.19%, first cycle 65.37% and in the second cycle it increased to 89.72%. Thus, the use of jigsaw type cooperative learning can be used as an alternative to improve student learning outcomes in Islamic religious education learning.